Effectiveness of Back Massage Acupressure for Treating Dysmenorrhea - Triana Septianti Purwanto; Feby Angzila Fatmayati; Tri Kurnia Rahayu (Knowledge Dynamics, 2025)
Background: Back massage acupressure is a natural complementary technique that minimizes side effects and can be administered to teenage girls experiencing dysmenorrhea. This technique was performed during the menstrual cycle, specifically from the 1st to the 3rd day, administered once a day for approximately 30 minutes. The novelty of the study lies in the complementary combination of a back massage and acupressure to reduce menstrual pain. This study aimed to analyze the effectiveness of back massage acupressure in reducing the intensity of pain and the duration of dysmenorrhea. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted on 60 teenage girls in the Magetan district. Systematic random sampling was used to select 30 respondents for both the intervention and control groups. Data were obtained from observations and interviews with respondents regarding the intensity of pain and duration of dysmenorrhea. Results: Back mass acupressure effectively reduces the intensity of dysmenorrhea pain from the 1st to 3rd day (p-value= 0.000) and shortens the duration of dysmenorrhea (p-value <0.05), thereby improving adolescent reproductive health. Conclusions: Back massage acupressure is a simple, cost-effective, and minimally invasive solution for managing dysmenorrhea. This innovative technique has been proven highly effective in reducing both the intensity of pain and the duration of dysmenorrhea. It is recommended for use among teenage girls to promote better reproductive health.